2011
DOI: 10.1002/pola.24696
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effect on performance and morphology of photovoltaic devices based on poly(3‐hexylthiophene)‐b‐poly(ethylene oxide)

Abstract: Novel block copolymers, poly(3‐hexylthiophene)‐b‐poly(ethylene oxide) (P3HT‐b‐PEO) were synthesized via Suzuki coupling reaction of P3HT and PEO homopolymers. The copolymers were characterized by NMR, gel permeation chromatography, differential scanning calorimeter, and UV–vis measurements. A series of devices based on the block copolymers with a fullerene derivative were evaluated after thermal or solvent annealing. The device using P3HT‐b‐PEO showed higher efficiency than using P3HT blend after thermal annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
1
39
0
1
Order By: Relevance
“…AFM measurement of the thin film based on P3HT-b-PEO/PCBM revealed that the introduction of PEO segment contributed to generate ordered lamellar morphology with the smaller size compared with the P3HT/PCBM blend. 133 The block copolymer P40 reported by Chen showed phase segregation on the devices. 134 During polymer deposition by spin-coating, the fluorinated block segregated on the surface of P3HT.…”
Section: P3ht Materials In Bulk Heterojunction Solar Cellsmentioning
confidence: 99%
“…AFM measurement of the thin film based on P3HT-b-PEO/PCBM revealed that the introduction of PEO segment contributed to generate ordered lamellar morphology with the smaller size compared with the P3HT/PCBM blend. 133 The block copolymer P40 reported by Chen showed phase segregation on the devices. 134 During polymer deposition by spin-coating, the fluorinated block segregated on the surface of P3HT.…”
Section: P3ht Materials In Bulk Heterojunction Solar Cellsmentioning
confidence: 99%
“…insulating blocks as for example PMMA (P3HT-b-PMMA), [224] or poly(2-vinylpyridine) (P3HT-b-P2VP, [225][226][227][228][229] or P4VP (P3HT-b-P4VP), [230][231][232] or PEO (P3HT-b-PEO), [233][234][235][236][237][238][239][240][241][242] or polylactides (P3HT-b-PLA), [243] or polyacrylic acids (P3HT-b-PAA). [244,245] Also more special block copolymer with P3HT block were reported as for example azobenzene liquid crystalline mesogen, 6-(4-((4-methoxyphenyl)diazenyl)phenoxy)hexyl methacrylate (MMAZO) incorporated into a block copolymer with P3HT.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In order to create the linkage between P3AT and anionically‐prepared polymer segments, Tsuchiya, Ogino, and coworkers utilized the Suzuki‐Miyaura coupling reaction. As shown in Scheme , α‐bromo‐chain‐end‐functional P3HT was coupled by ω‐boronic‐ester‐chain‐end‐functional PEO, resulting in the formation of an arylene‐type CC bond to synthesize P3HT‐ b ‐PEO . Very recently, the same group reported the synthesis of P3HT‐ b ‐PDMS by an addition reaction based on hydrosilation using a platinum catalyst (Scheme ) .…”
Section: Synthesis Of P3at‐based Block Copolymers By Combination Of Lmentioning
confidence: 99%